2019
DOI: 10.3390/app9061123
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Based Approach for Multi-Label Emotion Classification in Tweets

Abstract: Currently, people use online social media such as Twitter or Facebook to share their emotions and thoughts. Detecting and analyzing the emotions expressed in social media content benefits many applications in commerce, public health, social welfare, etc. Most previous work on sentiment and emotion analysis has only focused on single-label classification and ignored the co-existence of multiple emotion labels in one instance. This paper describes the development of a novel deep learning-based system that addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 29 publications
0
49
0
1
Order By: Relevance
“…The most famous usage of this analysis is the detection of sentiment on Twitter. In recent work, Mohammed et al proposed an automatic system called a Binary Neural Network (BNet) to classify multi-label emotions by using deep learning for Twitter feeds [18]. They conducted their work on emotion analysis with the co-existence of multiple emotion labels in a single instance.…”
Section: Human Emotionsmentioning
confidence: 99%
“…The most famous usage of this analysis is the detection of sentiment on Twitter. In recent work, Mohammed et al proposed an automatic system called a Binary Neural Network (BNet) to classify multi-label emotions by using deep learning for Twitter feeds [18]. They conducted their work on emotion analysis with the co-existence of multiple emotion labels in a single instance.…”
Section: Human Emotionsmentioning
confidence: 99%
“…Therefore, the proposed approach is a data analysis technique that should be useful to those who seek to use UGC to improve their communication or marketing strategies. Also, it should be useful to educational institutions that may be able to enhance their offerings by identifying needs and trends based on technologies previously investigated [52][53][54][55]. Figure 1 shows the training process of the SVM algorithm and the classification according to the feelings that (a) represents the training process of a sentiment analysis algorithm with a feature extractor and a machine learning algorithm, and (b) represents the prediction process of a sentiment analysis algorithm with a feature extractor and a classifier model [2].…”
Section: Knowledge-based Methods To Extract Insights From Ugcmentioning
confidence: 99%
“…Results showed that the more sensitive an individual is, the more health care is considered. Jabreel et al [23] proposed a multi-labeled sentiment analysis on social media with deep learning. They restructured the multi-label problem to a single binary issue, then applied deep learning.…”
Section: Related Workmentioning
confidence: 99%